Pharmacological activities of pyrazolone derivatives - Parajuli, Rishi Ram; Pokhrel, Priyanka; Tiwari, Amish Kumar; Banerjee, Janmajoy (Creative Pharma Assent, 2013)
Pyrazoline is a five member heterocyclic ring which is a versatile lead compound for designing potent bioactive agents. The review of the literature shows that the pyrazoline derivatives are quite stable and has inspired the chemists to synthesize the new pyrazoline derivatives. The past studies of pyrazoline derivative revealed that they are useful in pharmaceutical and agrochemical research. Pyrazoline derivatives display various pharmacological activities such as antitumor, antitubercular, antimicrobial, antibacterial, anti-inflammatory and antioxidant etc. and the pharmacological activities of different synthesized compound are reviewed in the present article.